Multimodal endoscope can quantify wide-field fluorescence detection of Barrett’s neoplasia - Joshi, Bishnu P.; Duan, Xiyu; Kwon, Richard S.; Piraka, Cyrus; Elmunzer, B. Joseph; Lu, Shaoying; Rabinsky, Emily F.; Beer, David G.; Appelman, Henry D.; Owens, Scott R.; Kuick, Rork; Doguchi, Nobuyuki; Turgeon, D. Kim; Wang, Thomas D. (Endoscopy, 2016)
Background and study aims: To demonstrate the clinical use of a multimodal endoscope with a targeted fluorescently labeled peptide for quantitative detection of Barrett’s neoplasia.Patients and methods: We studied 50 patients with Barrett’s esophagus using a prototype multimodal endoscope with a fluorescently labeled peptide. Co-registered fluorescence and reflectance images were converted to ratios to correct for differences in distance and geometry over the image field of view. The ratio images were segmented using a unique threshold that maximized the variance between high and low intensities to localize regions of high grade dysplasia (HGD) and esophageal adenocarcinoma (EAC).Results: Early neoplasia (HGD and EAC) was identified with 94 % specificity and 96 % positive predictive value at a threshold of 1.49. The mean results for HGD and EAC were significantly greater than those for squamous/Barrett’s esophagus and low grade dysplasia by one-way analysis of variance (ANOVA). The receiver operator characteristic curve for detection of early neoplasia had an area under the curve of 0.884. No adverse events associated with the endoscope or peptide were found.Conclusion: A multimodal endoscope can quantify fluorescence images from targeted peptides to localize early Barrett’s neoplasia. (ClinicalTrials.gov number NCT01630798.)